Studying on the frost damage of some peach and nectarine varieties - Dani, Mária; Thurzó, Sándor; Racskó, József; Drén, Gábor (Acta Agraria Debreceniensis, 2006)
To be able to grow stone fruit species, the peach and the nectarine varieties, yield stability is very relevant. However, the climate is suitable in Hungary for growing stone fruits. We have to calculate with damage. Important winter damage and spring frost damage occur in every second year on the Great Pplains. To reveal the frost tolerance of cultivars and to clarify the differences among growing areas is the most important point of peach and nectarine production. We, made our experiments in the winter of 2005 (January-February), at Pallag, Zsombó, Siófok, Sóskút and Szatymaz. These former places are determinant in peach and nectarine growing in Hungarian respects. In our experiments we analyzed 10-10 fruit shoot from 82 varieties, and we measured the frost damage and the flower bud density. The minimum and the maximum frost damage values (%) at the different growing places were 7.6-38.7 at Siófok, 6.5-31.3 at Sóskút, 34.3-100 at Szatymaz, 83.7-99.6 at Pallag and 51.9-99.6 at Zsombó. There were expressive differences between the same cultivars depending on the growing area. The frost damage of „Suncrest” variety was 7.6% at Siófok, 8.2% at Sóskút but it was 69.8% at Szatymaz. The „Maystar” variety had 17.6% at Siófok, 12.4% at Sóskút and 87.2% frost damage at Szatymaz. In case of „Redhaven” variety the frost damage values were 16.8% at Sóskút, 54.6% at Szatymaz. We collected fruit shoots from three different heights in case of „Cresthaven” variety. In case of 1 meter height the frost damage was 74.6%, at 2 meter height 44.7%, and 25.2% at 3 meter. We experienced also big differences in flower bud density (flower bud/10 cm) of varieties. The following cultivars had the highest flower bud density (6-7 bud/10 cm): „Suncrest”, „Meystar, „Maria Luisa” and the „Maria Bianca”, „Redhaven”, „Michellini” had the lowest flower bud density (2-3 bud/10 cm). After our experiments we established that there were very expressive differences among the frost damage of peach and nectarine varieties from different climatic conditions and there are also big variance between the frost damage values of those fruit shoots, what were collected from different heights, but from the same variety. It conspicuous very good among our items, that difference of the flower bud density is very big among the varieties.To be able to grow peach and nectarine successfully, the suitable variety (low frost damage value, high flower bud density) and the suitable growing are is determinant.